Carbon source–dependent capsule thickness regulation in Streptococcus pneumoniae - Werren, Joel P.; Mostacci, Nadja; Gjuroski, Ilche; Holivololona, Lalaina; Troxler, Lukas J.; Hathaway, Lucy J.; Furrer, Julien; Hilty, Markus (Frontiers in Cellular and Infection Microbiology, 2023)
Background The polysaccharide capsule of Streptococcus pneumoniae plays a major role in virulence, adherence to epithelial cells, and overall survival of the bacterium in the human host. Galactose, mannose, and N-acetylglucosamine (GlcNAc) are likely to be relevant for metabolization in the nasopharynx, while glucose is the primary carbon source in the blood. In this study, we aim to further the understanding of the influence of carbon sources on pneumococcal growth, capsule biosynthesis, and subsequent adherence potential. Methods We tested the growth behavior of clinical wild-type and capsule knockout S. pneumoniae strains, using galactose, GlcNAc, mannose, and glucose as carbon source for growth. We measured capsule thickness and quantified capsule precursors by fluorescein isothiocyanate (FITC)–dextran exclusion assays and 31P-nuclear magnetic resonance measurements, respectively. We also performed epithelial adherence assays using Detroit 562 cells and performed a transcriptome analysis (RNA sequencing). Results We observed a reduced growth in galactose, mannose, and GlcNAc compared to growth in glucose and found capsular size reductions in mannose and GlcNAc compared to galactose and glucose. Additionally, capsular precursor measurements of uridine diphosphate-(UDP)-glucose and UDP-galactose showed less accumulation of precursors in GlcNAc or mannose than in glucose and galactose, indicating a possible link with the received capsular thickness measurements. Epithelial adherence assays showed an increase in adherence potential for a pneumococcal strain, when grown in mannose compared to glucose. Finally, transcriptome analysis of four clinical isolates revealed not only strain specific but also common carbon source-specific gene expression. Conclusion Our findings may indicate a careful adaption of the lifestyle of S. pneumoniae according to the monosaccharides encountered in the respective human niche.